Analisis Usability terhadap User Experience pada aplikasi Tierra menggunakan metode USE Questionnaire - Ivan Pratama Yunus; Hasniati; Syamsul Bahri (STMIK KHARISMA Makassar, 2023)
This study aims to analyze the level of usability of the Tierra application on the user experience. Tierra is an application created as a communication media solution for ornamental plant lovers. Therefore, this study was conducted to measure the usability of the Tierra application with the aim of knowing the level of effectiveness, efficiency and user satisfaction in using the application. The method used in this study is a USE Questionnaire which has 4 parameters, namely usefulness, ease of use, ease of learning, and satisfaction. The results of usability measurements obtained the percentage of feasibility of each variable, namely usefulness with a percentage of 82.33%, ease of use with a percentage of 86.30%, ease of learning with a percentage of 87.17%, and satisfaction with a percentage of 70.76% from these results it is known that these variables are in the feasible category. The results of the calculation of all variables using a Likert scale obtained a percentage score of 84.57%, thus it can be concluded that the Tierra application has met the standards on the USE Questionnaire parameters.